Avaliação da atividade urinária das enzimas gama-glutamiltransferase e fosfatase alcalina para a detecção da nefropatia em pacientes com diabetes Mellitus tipo 2 - Carvalho, José Antonio Mainardi de (2011)
Background: Diabetic nephropathy (DN) is defined as a rise in urinary albumin excretion rate, often associated with an increase in blood pressure. It is the leading cause of end-stage renal disease and carries an increased risk for cardiovascular mortality. Microalbuminuria is the first sign of diabetic renal impairment or incipient nephropathy and is generally considered the best noninvasive predictor for the development of DN. Urinary markers of tubular damage are mainly composed of enzymes or plasma proteins of low molecular weight that are normally freely filtered by the glomerulus, and these biomarkers can be useful for diagnosis of DN. Thus, the aim of this study was to test the diagnostic accuracy of the urinary excretion of gama-glutamyltransferase (GGT) and alkaline phosphatase (ALP) for diagnosis of diabetic nephropathy (DN). Methods: Fasting glucose, fructosamine, serum creatinine, glomerular filtration rate (GFR), serum uric acid, serum albumin, and urinary albumin, creatinine, GGT and ALP were assessed in 74 type 2 diabetic patients without nephropathy and 38 type 2 diabetic patients with nephropathy. Results: Urinary GGT and ALP were threefold higher in type 2 diabetic patients with nephropathy. Significant correlations were observed between urinary albumin and GGT (r=0.439, P<0.001) and urinary albumin and ALP (r=0.305, P<0.01). Areas under the curve for GGT and ALP were 0.7696 (P<0.001) and 0.7233 (P<0.001), respectively. At a cut-off value of 72 U/g creatinine, GGT demonstrated a sensitivity of 96.0% and a specificity of 52.6%. At a cut-off value of 20 U/g creatinine, ALP demonstrated a sensitivity and specificity of 83.8% and 36.8%, respectively. Conclusions: Urinary GGT and ALP have potential value in the diagnosis of nephropathy in type 2 diabetic patients, but GGT has a slightly higher ability to discriminate nephropathy than ALP.